Asymptomatic diffuse "encephalitic" cerebral toxoplasmosis in a woman with systemic lupus erythematosus. (July 2016) - Murro, Diana; Novo, Jorge; Arvanitis, Leonidas
Highlights: This is the first reported lupus patient with diffuse non-necrotizing cerebral toxoplasmosis. Affected patients lack of neurologic symptoms and show no focal lesions on brain imaging. This disease is rapidly progressive and has only been diagnosed on autopsy. Abstract: Classic cerebral toxoplasmosis typically presents with neurologic symptoms such as seizures and mental status changes and histological examination shows focal lesions with necrosis. However, in the diffuse "encephalitic" form, patients are asymptomatic with diffuse, inflammatory, non-necrotic lesions. Asymptomatic diffuse "encephalitic" toxoplasmosis has been reported only in four acquired immunodeficiency syndrome patients and one human immunodeficiency virus (HIV) negative patient with chronic lymphocytic leukemia. We present a 36-year-old HIV-negative woman with systemic lupus erythematosus and lupus nephritis who was on immunosuppression for 9 years after cadaveric renal transplant and died from pulmonary hemorrhage and cytomegalovirus pneumonia. Brain autopsy findings revealed multifocal microglial nodules containing Toxoplasma bradyzoites and associated astrogliosis. These nodules were prominent in the cerebellum, midbrain and medulla and also present in the cortex and thalamus. No coagulative necrosis, necrotizing abscesses, or other opportunistic infections were present. The patient had previously exhibited no neurologic symptoms and there was no clinical suspicion for toxoplasmosis. To the best of our knowledge, this is the first case of diffuse, non-necrotizing, "encephalitic" cerebral toxoplasmosis reported in a lupus patient and also the first reported female case.